Legalización e inscripción de la unión de hecho en el registro civil, identificación y cedulación. - Guerrero Jiménez, Katherine Vanessa (2014)
In our constitutional rights and guarantees state of families formed in de facto unions are protected as provided in Art. 68 of our Constitution in which reads "The stable and monogamous union between two people free of marriage to form a home-made, for the period and under the conditions and circumstances that the law will generate the same rights and obligations as those of families constituted by marriage. Before the 1978 constitution extramarital families had no protection in the patrimonial order.